Optimalisasi Regulasi Perbankan Untuk Mempercepat Transformasi Digital di Indonesia - Tarantang, Jefry; Putri, Meyrara Widya (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2025)
This study explores efforts to optimize banking regulations as a strategy to accelerate digital transformation in Indonesia. This research uses a descriptive qualitative method, a normative juridical legal approach with literature studies on changes in banking regulations and digital transformation, as well as case studies related to the implementation of regulations in the Indonesian banking sector. The analysis results show that adequate banking regulations can accelerate digital transformation by creating a conducive environment for innovation and investment in the banking sector. However, challenges in optimizing banking regulations are also faced, including limited understanding of technology by regulators and limited infrastructure. This research concludes that to achieve a faster and more inclusive digital transformation in the Indonesian banking sector, a regulatory approach that is progressive and responsive to technological dynamics is needed. Strategic steps include increasing regulatory capacity, partnerships between government, industry and other stakeholders, as well as a regulatory framework that enables innovation while maintaining the security and reliability of the financial system.